Chemical communication in the Genus Anguilla: a minireview - Hubbard, Peter (2014)
Eels of the Genus Anguilla are important fish in both scientific and economic terms. Unfortunately, current stocks of the European eel in particular (Anguilla anguilla L.) are becoming increasingly endangered. Chemical communication plays important roles in several key aspects of fish biology. Due to its complex life-cycle, the eel offers a unique opportunity to study various aspects of olfactory biology and chemical communication almost in isolation, feeding (during freshwater ‘yellow’ stage), adaptation to seawater, migration and, finally, reproduction. The aim of this brief review is to summarise what is known about chemical communication in the eel (during reproduction in particular) and, more importantly, stimulate further research. To date, eels have been shown to have high olfactory sensitivity to substances released by conspecifics. Both the bile fluid and skin mucus have been implicated as the routes of release of these odorants but other routes, such as the urine, cannot be excluded. Furthermore, the nature of these odorants depends on both the sex and reproductive status of the donor; exposure to water conditioned by mature con-specifics causes a stimulation of sexual maturation in immature eels. These results are consistent with a role for chemical communication in eel reproduction. The European eel is, therefore, proposed as a model species for studies on olfaction and chemical communication in fish because of its ancestral status, its high olfactory sensitivity and its physiological plasticity. However, more research is necessary; specifically, identification of the key odorants involved, their behavioural and physiological effects and how the olfactory system may change at various stages of its life-cycle.